2017
DOI: 10.20944/preprints201701.0047.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On <em>ev</em>-degree and <em>ve</em>-degree topological indices

Abstract: Recently two new degree concepts have been defined in graph theory: ev-degree and ve-degree. Also the evdegree and ve-degree Zagreb and Randić indices have been defined very recently as parallel of the classical definitions of Zagreb and Randić indices. It was shown that ev-degree and ve-degree topological indices can be used as possible tools in QSPR researches . In this paper we define the ve-degree and ev-degree Narumi-Katayama indices, investigate the predicting power of these novel indices and extremal gr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…It was suggested in [30] that these novel degree concepts may be used to define novel degree based topological indices. Following this suggestion, ev-degree and ve-degree topological indices have been defined in [31], [32], [33], [34]. These novel ev-degree and ve-degree topological indices have been showed that give considerably good correlations to predict some physicochemical properties of octane molecules than wellknown and above mentioned topological indices; Wiener, Zagreb and Randić indices.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested in [30] that these novel degree concepts may be used to define novel degree based topological indices. Following this suggestion, ev-degree and ve-degree topological indices have been defined in [31], [32], [33], [34]. These novel ev-degree and ve-degree topological indices have been showed that give considerably good correlations to predict some physicochemical properties of octane molecules than wellknown and above mentioned topological indices; Wiener, Zagreb and Randić indices.…”
Section: Introductionmentioning
confidence: 99%
“…The classical degree-based frameworks then have been transformed into ve-degree and ev-degree Zagreb and Randic indices in. [29][30][31] The ve-degree Zagreb index has been shown to have a greater predictive ability than the classic Zagreb index.…”
Section: Introductionmentioning
confidence: 99%
“…Novel ev-degree and ve-degree concepts were defined in (Chellali, et al, 2017). Moreover, novel ev-degree and ve-degree topological indices have been defined in Sahin and Ediz, 2018;Ediz, 2018).…”
Section: Introductionmentioning
confidence: 99%